Association of perfluoroalkyl substances exposure with reproductive hormone levels in adolescents: By sex status. (September 2016) - Zhou, Yang; Hu, Li-Wen; Qian, Zhengmin (Min); Chang, Jen-Jen; King, Chris; Paul, Gunther; Lin, Shao; Chen, Pau-Chung; Lee, Yungling Leo; Dong, Guang-Hui
Abstract: Polyfluoroalkyl substances (PFASs) are a group of common chemicals that ubiquitously exist in wildlife and humans. However, few studies have researched the effect of PFASs on reproductive hormones in adolescents. To provide information in this regard, we recruited 225 Taiwanese adolescents aged 13–15 years from 2009 to 2010 to investigate the relationship between serum PFASs (PFOS, PFOA, PFBS, PFDA, PFDoA, PFHxA, PFHxS, PFNA and PFTA) and reproductive hormone concentrations using a cross-sectional study design. Results showed PFOS and PFTA levels were highest among the PFASs, with a median concentrations of 29.9 (interquartile range: 13.0–43.8) ng/mL and 6.0 (0.6–25.9) ng/mL in males, and a median concentrations of 28.8 (14.8–42.6) ng/mL and 4.5 (0.3–18.4) ng/mL in females. After adjustment for confounding factors, nonsignificant associations between PFASs and reproductive hormone were found except for PFNA with ln(estradiol) (β = 0.2060, 95%CI: 0.0016, 0.4105). When stratified by sex, more significant associations were found in males than in females. Among males, PFASs were negatively associated with ln(testosterone) level for PFOS (β = − 0.0029, 95%CI: − 0.0055, − 0.0003), PFDA (β = − 0.2565, 95%CI: − 0.4135, − 0.0994), PFHxA (β = − 0.3095, 95%CI: − 0.5942, − 0.0248), and PFNA (β = − 0.4233, 95%CI: − 0.6998, − 0.1467). Furthermore, male participant ln(estradiol) levels were positively associated with PFOA (β = 0.0921, 95%CI: 0.0186, 0.1656), and PFHxS (β = 0.0462, 95%CI: 0.0020, 0.0905). Among females, a significant relationship was found only for PFDoA with ln(testosterone) (β = − 0.0119, 95%CI: − 0.0227, − 0.0010). In conclusion, this study showed higher levels of PFASs coincide with lower testosterone and higher estradiol levels, and more significant associations of PFASs with reproductive hormone were found in males than in females. Highlights: Few human studies reported the association between PFASs and productive hormones. The association between serum PFASs with serum hormones were evaluated in children. PFASs associated negatively with testosterone and positively with estradiol levels. More significant associations were found in males than in females.